Improvement of Flexural Behavior of Reinforced Concrete Cantilever Hollow Beam by Using Carbo-DUR CFRP - et. al, Ahmed Salim Edan (International Journal of Advanced Science and Technology, 2019)
The present research studied experimental and theoretical investigations that showed the effect of two variables have major influence toward improving the flexural behavior. Such as the effect of hollow length and the strengthenning by using CFRP laminate of reinforced concrete cantilever beams.The experimental work showed two important characteristics, one of them was the small effect of hollow beam sections in decreasing the flexural strength and the other significant thing was the increased flexural strength due to adding the CFRP laminate, which placed at the top concrete beam surface. Experimental results clarified the main role of using CFRP laminate through increasing the yield strength by about three times toward more rigidity and increasing the ultimate strength by about two times of solid beam through decrasing the ductility of the beam from (1.15 to 1.09) with and without CFRP laminate respectively. For beams of hollow length equal to o.5m the major increment for the ultimate load, which reached approximately to two times and the ductility ranges as (13.5 to 13.58). Cantilever beam with a hollow length equal to 1m, CFRP laminate enhanced the flexural strength by increasing the final strength by about 1.63 times despite the small decreasing in the yield strength. So, their ductilities range as (10.4 to 10.6). The last group of cantilever beam with a fully hollow length, the clearance strengthening of the CFRP laminate through increasing the final strength up to 1.83 times the same cantilever beam without CFRP. Also, the ductility back to lowest values as same as the solid beam ductility with a range: 1.04 -1.06. Theoretical methods (ANSYS) for satisfying the results of complete study to make verification with results were obtained from both experimental and theoretical testing methods. All the comparisons results referred to the low differences between the experimental and ANSYS results for beams of normal reinforcement and additional strength by CFRP laminate. So, all the differnces were approximately near to 12% or less which are within the permitted from ACI 318M-14 code requirements.